Analysis of the primary responsibilities of team leaders in extreme Iraqi Context - Fares, Rabee; Valax, Marc (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This study analyzes how team leaders adapt their management style in extreme contexts, such as Iraq, where social tensions remain high. The study employs the High Leader-Member Exchange (H-LMX) theory, which posits that the quality of the exchange relationship between leaders and team members affects commitment and effectiveness. Through qualitative research, the study reveals a high level of LMX in wartime Iraq, where interviewees, who were leaders in their organizations, shared their experiences of the primary responsibilities they faced without support from supervisors during extreme events. Despite the dramatic context, the impact of leaders on their teams was key to achieving successful operations and performance.